Prevalence and associated factors of caesarian section in Ethiopia: a multilevel analysis of the 2019 Ethiopia Mini Demographic Health Survey - Samuel Hailegebreal; Girma Gilano; Binyam Tariku Seboka; Mohammedjud Hassen Ahmed; Atsedu Endale Simegn; Getanew Aschalew Tesfa; Delelegn Emwodew Yehualashet (BMC, 2021)
Abstract Background Caesarian section is a vital emergency obstetric intervention for saving the lives of mothers and newborns. However, factors which are responsible for caesarian section (CS) were not well established in the country level data. Therefore, this study aimed to assess the prevalence and associated factors of caesarian section in Ethiopia. Methods Data from the Ethiopian Mini Demographic and Health survey 2019 were used to identify factors associated with the caesarian section in Ethiopia. We applied multi-level logistic regression and a p-value of <0.25 to include variables before modeling and a p-value<0.05 with 95% confidence interval (CI) for final results. Result The prevalence of caesarian section in Ethiopia was 5.44% (95% CI; 0.048-0.06) in2019. Women in age group of 30-39 and 40-49 years had a higher odd of caesarian section (AOR = 2.14, 95%CI = 1.55-2.94) and (AOR = 2, 95%CI = 1.20-3.97) respectively compared to women in age group of 15-29 years. Women with secondary and higher educational level had higher odds of caesarian section (AOR = 2.15, 95%CI = 1.38-3.34) and (AOR = 2.8, 95%CI = 1.73-4.53) compared to those in no education category. Compared to Orthodox, Muslims and Protestant religions had lower odds of caesarian section with AOR of 0.50 (0.34-0.73) and 0.53 (0.34-0.85). Having <2 births was also associated with the low caesarian section 0.61(0.52-1.22). Using modern contraceptive methods, having ANC visits of 1-3, 4th, 5 plus, and urban residence were associated with higher odds of caesarian section as 1.4 (1.05-1.80]), 2.2 (1.51-3.12), 1.7 (1.12-2.46), and 2.4 (1.65-3.44) 1.6(1.04-2.57) respectively. Conclusion Although evidence indicates that the caesarian deliveries increased both in developed and underdeveloped countries, the current magnitude of this service was very low in Ethiopia which might indicate missing opportunities that might costing lives of mothers and newborns. Women's age, religion, educational status, parity, contraceptive method, and ANC visit were individual level factors influenced caesarian section. whereas, region and place of residence were community level factors affected caesarian section in the country. Depending on these factors, the country needs policy decisions for further national level interventions.